Tracking the Slowdown in Long-Run GDP Growth - Antolin-Diaz, Juan; Drechsel, Thomas; Petrella, Ivan (The Review of Economics and Statistics, 2017)
Using a dynamic factor model that allows for changes in both the long-run growth rate of output and the volatility of business cycles, we document a significant decline in long-run output growth in the United States. Our evidence supports the view that most of this slowdown occurred prior to the Great Recession. We show how to use the model to decompose changes in long-run growth into its underlying drivers. At low frequencies, a decline in the growth rate of labor productivity appears to be behind the recent slowdown in GDP growth for both the United States and other advanced economies. When applied to real-time data, the proposed model is capable of detecting shifts in long-run growth in a timely and reliable manner.